Manajemen Penagihan Pajak Aktif Di Kantor Pelayanan Pajak Pratama Jakarta Pademangan Tahum 2020 - Lely Naulul Muna; Selvi Selvi (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study was conducted with the aim of analyzing the management of active tax collection at the Primary Tax Office of Pademangan, Jakarta in 2020, the constraints of the tax authorities in the management of active tax collection at the Primary Tax Office of Pademangan, Jakarta, and the efforts made to overcome these obstacles. This study used a qualitative approach. The data collection was carried out through observation and in-depth interviews with tax collection department staff at the Primary Tax Office of Pademangan, Jakarta. The results of this study indicate that there were weaknesses in active tax collection management in 2020. The problem experienced by the Primary Tax Office of Pademangan, Jakarta was the insufficient human resources in the tax collection department, especially data processors whose existence was important as tax collection support. The COVID-19 pandemic was also a serious obstacle. Many taxpayers' businesses had to close due to the Large- Scale Social Restrictions implemented by the government, thus hampering the implementation of tax collection. Efforts made by the Primary Tax Office of Pademangan, Jakarta included coordinating with the Internal Data Processing Section in data processing. In addition, the Primary Tax Office of Pademangan, Jakarta also adapted to the pandemic by carrying out the direction of the Directorate General of Taxes regarding tax collection strategies during the pandemic. Suggestions from the author to improve the management of active tax collection at the Primary Tax Office of Pademangan, Jakarta include placing human resources who are experts in data processing or carrying out data processing training for existing human resources. In terms of the implementation of active tax collection strategies during the pandemic, the Primary Tax Office of Pademangan, Jakarta can focus on business sectors that are developing during the pandemic, including food, pharmaceuticals, health and information technology.